Zero day exploit countdown to darkness - Shein, Rob.; Sachs, Marcus H. (Rockland, MA : Syngress, 2004)
The realistic portrayals of researching, developing, and ultimately defending the Internet from a malicious "Zero-Day" attack will appeal to every corner of the IT community. Although finctional, the numerous accounts of real events and references to real people will ring true with every member of the security community. This book will also satisfy those not on the "inside" of this community, who are fascinated by the real tactics and motives of criminal, malicous hackers and those who defent the Internet from them. * The realistic portrayals of researching, developing, and ultimately defending the Internet from a malicious "Zero-Day" attack will appeal to every corner of the IT community. * This book will entertain, educate, and enlighten the security and IT community about the world of elite security professionals who safeguard the Internet from the most dangerous cyber criminals and terrorists. * Although finctional, the numerous accounts of real events and references to real people will ring true with every member of the security community.
"Rob Shein aka Rogue Shoten."
Title from e-book title screen (viewed Sept. 1, 2004).
"Foreword by David Litchfield."--E-book 'cover' p.
Keywords: Computer security -- Fiction; Computer hackers -- Fiction; Computer networks -- Security measures -- Fiction; Electronic books; Fiction